Prime bi-interior ideals of Γ-semirings - Marapureddy Murali Krishna Rao (Journal of Hyperstructures)
In this paper, we introduce the notion of prime bi-interior ideal, bi-interior ideal,strongly prime bi-interior ideal,semiprime strongly irreducible bi-interior ideal and irreducible bi-interior ideal.we study these ideals properties and relation between them and also characterize regular Γ-semiring and Γ-semiring using prime bi-interior ideals.